The ratio of specifc heat capacity, at constant presszrre to that at constant volume (cdc,J, of a gas can be determined by either the adiabatic expansion method or the sound velocity method. The objective of this experiment is apply the adiabatic expansion method for determining the specc heat capacity ratio of gas N2 and O2 The result showed that the ratio were 1.14 and 1.19 respectively for gas N2 and 02.T he value obtained by the experiment was d flerenta bout 15 to 19% from the result deter - Wiludjeng Trisasiwi; Dyah Wulandani; Kamaruddin Abdullah; Armansyah H Tambunan (PERTETA, 1998)
The ratio of specifc heat capacity, at constant presszrre to that at constant volume (cdc,J, of a gas can be determined by either the adiabatic expansion method or the sound velocity method. The objective of this experiment is apply the adiabatic expansion method for determining the specc heat capacity ratio of gas N2 and O2 The result showed that the ratio were 1.14 and 1.19 respectively for gas N2 and 02.T he value obtained by the experiment was d flerenta bout 15 to 19% from the result determined by theoretical method using 5 degree of Jkeedom. Theoretically cdc,, of both gas N2 and 0 2 which have 5 degree offreedom are 1.4. The dzflerence was considered to be caused by thee xperimental condition, which were not suflciently adiabatic, as required by the method. However, the simplicity of the method and clarity of its theoretical approach is advantageous to be used by students of Advance Thermodynamic class as a practical exercise.